The Melatonin and Enriched Environment Ameliorated Low Protein-Induced Intrauterine Growth Retardation by IGF-1 And mtor Signaling Pathway and Autophagy Inhibition in Rats - Wang, Dan; Wu, Xiao; Lu, Dan; Li, Yan; Zhang, Peng (Current Molecular Medicine, 2021)
Aim: The present study investigated whether melatonin (MEL) and enriched environment (EE) might protect against intrauterine growth retardation (IUGR) in rats. Methods: Sprague-Dawley rats were randomly allocated to 3 groups: control (C), model (M) and EE+MEL group. Animals were housed in an enriched environment (EE+MEL group) or remained in a standard environment (C group, M group). IUGR rat model was built by feeding a low protein diet during pregnancy. MEL was administered by gavaging. At day 1 post-birth, the baseline characteristics and serum biochemical parameters, morphology of liver and small intestine, enzyme activities, and mRNA expression levels of fetal rats were determined. The autophagy marker LC3 and Beclin1 were determined by western blot analysis. Results: EE+MEL markedly improved the baseline characteristics, hepatic and intestinal morphology of IUGR fetuses. In addition, the lactase activities in the fetal intestine were markedly increased by the EE+MEL. The levels of serum somatostatin (SST), Growth hormone (GH), GH releasing hormone (GHRH), Insulin-like Growth Factor 1 (IGF-1), triiodothyronine (T3), and tetraiodothyronine (T4) were found to be recovered by EE+MEL. In addition, the EE+MEL significantly ameliorated the mRNA expression of SST, GHRH, and GHRH receptor (GHRHR), GH, GHR, IGF-1, and IGF-1 receptor (IGF1R), IGF binding protein-1 (IGFBP1), mammalian target of rapamycin (mTOR), S6 kinase 1 (S6K1) and eukaryotic initiation factor 4E (eIF4E)-binding protein 1 (4EBP1) in fetuses. In IUGR fetal livers, LC3 and Beclin1 were found to be increased at birth, while LC3 and Beclin1 were observed to be significantly decreased in the EE+MEL group. Conclusion: EE+MEL could improve fetal rats' baseline characteristics, serum biochemical parameters, birth weight, intestinal and hepatic morphology and enzyme activities. These effects could be explained by the activation of the IGF-1/IGFBP1 and IGF-1/mTOR/S6K1/4EBP1 signaling pathway and autophagy inhibition.
Keywords: Autophagy